THE USE OF COMIC AS A LEARNING MEDIUM FOR ECOLOGY - Panjaitan, Ruqiah Ganda Putri; Lijana, Lijana; Wahyuni, Eko Sri (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
This research aimed to determine the feasibility of comics as media of learning on ecology materials in class X SMA. The research method was descriptive research and the descriptive research which used was survey method, while the research instrument was validation sheet. Assessment of validity was done by 5 validators. The media validation sheet consists of seven aspects: physical, design and color, drawing and writing, material content, conformity with learning objectives, simplicity, also messaging design elements. The results showed that the average validation of each aspect was 0.99 and CVI value (content validity index) also 0.99. It can be concluded that the comics is valid to use as a media in learning on ecology materials.